2014
DOI: 10.1024/0036-7281/a000625
|View full text |Cite
|
Sign up to set email alerts
|

Klauengrösse von Schottischen Hochland-Kühen nach Weide- und Laufstallhaltung

Abstract: The claws of pastured Scottish Highland Cattle are large and this may raise the question if regular claw trimming is necessary. Therefore, the claws of the right thoracic and pelvic limbs were measured in 22 Scottish Highland cows 4 times 8 weeks apart. The cows were kept on various alpine pastures before the first measurement, on a two-hectare low-land pasture before the second measurement, in a welfare-compliant straw-bedded free stall before the third measurement and on alpine pasture before the fourth meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The similar weight-claw allometry of the two productive breeds goes along with Tuohy et al ( 33 ), who found only small differences in weight-claw allometry between Holstein and Holstein × Jersey dairy cows. The relatively large claws of Highland cattle have been presumed ( 34 ), but have never been quantified in a comparative assessment. For this experiment, cows where kept under similar, but not identical housing condition over winter.…”
Section: Discussionmentioning
confidence: 99%
“…The similar weight-claw allometry of the two productive breeds goes along with Tuohy et al ( 33 ), who found only small differences in weight-claw allometry between Holstein and Holstein × Jersey dairy cows. The relatively large claws of Highland cattle have been presumed ( 34 ), but have never been quantified in a comparative assessment. For this experiment, cows where kept under similar, but not identical housing condition over winter.…”
Section: Discussionmentioning
confidence: 99%